Public Legal Awareness of the Fixed Object Waqf Paradigm Towards Progressive Waqf - Hariyanto Hariyanto (International Journal of Social Science and Religion (IJSSR), 2022)
This study aims to determine the factors that influence changes in the legal awareness of the community and nazhir in Bantul Regency towards the paradigm of fixed object waqf towards progressive waqf. The type of research is a field study. The method uses descriptive qualitative juridical data analysis. The primary data is conducted by interviewing the respondents with purposive sampling. The results showed that three determinant factors influenced the progressive waqf paradigm: 1) Public understanding of waqf property was limited to fixed objects (unmovable objects). 2) Public understanding of the allocation of waqf property is limited to educational and worship facilities. 3) Public understanding of the waqf reward is limited to education and worship.